Role of Security Agencies in Cubing Election Violence in Nigeria - Abdullahi, Danjuma; Baba, Yahaya T.; Musa, Aminu (International Journal of Social and Administrative Sciences, 2016)
The paper examines the role of security agencies in cubing election violence in Nigeria using Kebbi state as a case study. Previous studies only discussed role of security agencies in maintaining law and order without mentioning their role especially during elections, therefore this research intends to close the gap. Data were sourced through interviews conducted with the stake holders such as staff of the electoral institution, civil society, security agencies such as the Police, Nigerian Security and Civil Defence Corps as well as Nigerian Prisons Service and Non governmental Organizations such as Vigilante group. The findings show that politicians are conniving with securities especially the government in power during transition period in order to win election leading to massive destruction as well as loss of lives and properties. The paper gives some recommendations on how to improve the situation.